Safety Perception and Gendered Use of Urban Green Parks (UGP): An Investigation of Impact on Visitation Patterns - Suhani Jain; Neha Pranav Kolhe (Calibrating Urban Livability in the Global South, 2024)
Urban Green Parks (UGP) holds an important position in society which helps in improving human’s quality of life and uplifting many aspects of human and environment health. However, accessibility and distribution of these spaces has always been unequal to various social groups, with ignoring important factors such as gendered perception of safety. To understand sense of security, five factors are considered: visibility, lighting, cleanliness and hygiene, external security (CCTV, Neighborhood facing, etc.), mobility facilities. This paper aims to get insights on causes that leads to gender’s perceived fear in Urban Green Parks (UGP) and outline potential development solutions. This research employs physical surveys (N= 120, men and women) to understand residents’ perception and their requirement. The findings suggests that factors contributing to gendered perceived fear in UGPs. Women participants emphasized on lack of visibility, insufficient lighting and external security along with lack of hygiene in these public spaces as the factors that develops a sense of fear in them to use such spaces. Another essential need that came into focus was the availability of mobility amenities that are both inclusive and accessible. These research findings help in understanding the perception and need of UGP users which helps policymakers, urban planners and local authorities for developing gender-responsive strategies.